Monetary policy : goals, institutions, strategies, and instruments - Bofinger, Peter; Reischle, Julian; Schächter, Andrea (Oxford ; New York : Oxford University Press, 2001)
"This book provides an in-depth description and analysis of monetary policy in Europe and the United States. Focusing specifically on the European Central Bank, it offers one of the first comprehensive guides to understanding the targets, strategy, and instruments of the ECB." "Readership: Investment bankers and other professional investors, central bankers, academics and advanced level students in the field of monetary policy."--Jacket.
Includes bibliographical references and index.
opc 28/10/16
Loans
Keywords: Monetary policy; European Central Bank; Monetary policy - Europe; Monetary policy - United States; Europe; United States of America